Similarities and differences of case in English and Uzbek languages - Mustafoyeva Moxlaroyim Alisher qizi, Hasanova Xurshidabonu Baxtiyorovna, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
The examination of the degree of case is a subject of considerable academic interest, as it offers valuable insights into the similarities and differences of case. This article aims to explore the perspectives of both English and Uzbek scholars on this linguistic phenomenom. By delving into relevant theories and drawing upon examples from English and Uzbek literature, we endeavor to compare and contrast the terminologies and approaches employed in each language.